Refractory and Relapsing Laryngeal Edema Possibly Associated With Chronic Tonsillitis and Mycoplasma Infection, Requiring Reintubation and Tracheostomy - Yutaka Tsukamoto; Takashi Sugimoto; Masataka Umeda; Yuki Furuse; Haruo Yoshida; Yuka Nagae; Yasuo Ohsato; Yukitaka Ueki; Maeda Takahiro; Koya Ariyoshi (Case Reports in Medicine)
Relapsing epiglottitis has rarely been reported, and its etiology is not well established. A 44-year-old previously healthy Japanese man presented with a quickly progressing choking sensation. He had been experiencing refractory and relapsing laryngeal edema and probably acute epiglottitis (three episodes within 2 weeks), with rash and elevated pancreatic amylase. The patient required immediate intubation. After the initial extubation, he required reintubation and a subsequent tracheostomy. Antibiotics, glucocorticoid, and antihistamines were administered, and he finally recovered with the tracheostomy’s closure. Potential causes of this patient’s relapsing epiglottitis are as follows: persistent right swollen tonsil; a positive result on a Mycoplasma pneumoniae antigen test and a particle agglutination (PA) test, implicating chronic tonsillitis; and/or Mycoplasma infection. This is the first case report of refractory and relapsing epiglottitis requiring reintubation possibly concurrent with chronic tonsillitis and Mycoplasma infection.